Franz Liszt, his circle, and his elusive oratorio - Puslowski, Xavier Jon (Rowman and Littlefield, 2014)
In this book, Xavier Puslowski presents a detailed study of the links between Liszt, his contemporaries, and his milieu. Using Saint Stanislas Oratorio as a focal point, Puslowski draws together the history of the Romantic period in classical music, and key figures and historical events in his story of Liszt's achievements.